Wit - Edson, Margaret 1961- (HBO, 2010)
An English professor, who alienates her students, has always had control over her life. That is until she is diagnosed with a devastating illness. She agrees to undergo a series of procedures that are brutal, extensive and experimental. She finds that the fine line between life and death can only be walked with wit.
Orig.: USA, 2001
Keywords: Melodramas; Drama; Fernsehfilm; Film; DVD-Video